THE STUDY OF LITERACY CULTURE THROUGH ANDROID-BASED WEBTOON APPLICATION AS AN EFFORT TO IMPROVE ENGLISH CAPABILITY OF HIGH SCHOOL STUDENTS IN PANDEMIC TIMES - Khudlori, Amin; Efendi, Achmad Bahtiar (English Literature Department, Faculty of Economics, Law, and Humanities, 2022)
Webtoon is a type of comic currently in demand by young people (students). If it is used properly, webtoon can be used as one of the teaching media in learning English. In addition to improve English competence, the efforts to foster literacy culture in students are grown here. With the development of android-based mobile phones that are easy to use by students, researchers combine android-based application with webtoon learning media to improve students' English competence and literacy. The problem in this research is how to increase reading interest in high school students through android-based interactive learning media during the pandemic. This study aims to develop android-based interactive learning media through webtoon application as an effort to improve the English language skills of high school students through literacy culture during the pandemic. This study also aims to foster reading interest in high school students through smartphone technology. The subjects of this study were high school students. The research method used is triangulation method which includes data triangulation, inter-researcher triangulation and theoretical triangulation. The data collection techniques used were interview, observation and documentation which were analyzed with descriptive qualitative analysis techniques. The results showed that the respondents' English skills and reading interest increased with the use of the webtoon application. Based on the results of the study, it can be concluded that the use of android-based webtoon application makes students not only learn the existing material, but can also increase their reading interest.